2017
DOI: 10.1080/15402002.2016.1276019
|View full text |Cite
|
Sign up to set email alerts
|

Social Support, Insomnia, and Adherence to Cognitive Behavioral Therapy for Insomnia After Cancer Treatment

Abstract: Objective/Background While cognitive-behavioral therapy for insomnia (CBT-I) has been shown to be efficacious in treating cancer survivors’ insomnia, 30–60% of individuals have difficulty adhering to intervention components. Psychosocial predictors of adherence and response to CBT-I, such as social support, have not been examined in intervention studies for cancer survivors. Participants Datafroma randomized placebo-controlled 2 × 2 trial of CBT-I and armodafinil (a wakefulness promoting agent) were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…The ISI (10) is a seven-item instrument for insomnia assessment utilizing a 5-point Likert scale (0-4, not at all to extremely). The insomnia status was divided into no sleep difficulties (0-7), mild (8)(9)(10)(11)(12)(13)(14), moderate (15)(16)(17)(18)(19)(20)(21), and severe insomnia (22)(23)(24)(25)(26)(27)(28). The respondents whose scores were higher than 7 in ISI were thought to have sleep problems.…”
Section: Psychological Status Evaluationmentioning
confidence: 99%
“…The ISI (10) is a seven-item instrument for insomnia assessment utilizing a 5-point Likert scale (0-4, not at all to extremely). The insomnia status was divided into no sleep difficulties (0-7), mild (8)(9)(10)(11)(12)(13)(14), moderate (15)(16)(17)(18)(19)(20)(21), and severe insomnia (22)(23)(24)(25)(26)(27)(28). The respondents whose scores were higher than 7 in ISI were thought to have sleep problems.…”
Section: Psychological Status Evaluationmentioning
confidence: 99%
“…For example, it has been documented that high levels of social support attenuate insomnia and fatigue symptoms associated with stress (13)(14)(15). In particular, previous studies have reported that organizational support improves job satisfaction for HCWs with high burnout levels (16).…”
Section: Introductionmentioning
confidence: 99%
“…The subscales of anxiety and depression were scored separately by summing the items and then classifying as follows: normal (0-7), possible (8)(9)(10) and con rmed (≥ 11) [8]. For a relevant analysis, both scales were splited on moderate (11)(12)(13)(14), severe (15)(16)(17)(18)(19)(20)(21) [8].…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study with a long-term follow-up for patients showed that family support was associated with both low levels of, and quick improvement from, depression [16]. Kamen et al [17] showed that family support was related to less severe insomnia at baseline in BC patients. Additionally, one previous study demonstrated that family support could avoid or alleviate certain mood di culties in BC patients in the Chinese population [18].…”
Section: Discussionmentioning
confidence: 99%